Increased serum IgG and IgA in overweight children relate to a less favourable metabolic phenotype. Issue 3 (2nd April 2013) - Bassols, J.; Prats‐Puig, A.; Gispert‐Saüch, M.; Crehuet‐Almirall, M.; Carreras‐Badosa, G.; Díaz‐Roldán, F.; Montesinos‐Costa, M.; de Zegher, F.; Ibáñez, L.; López‐Bermejo, A.
Summary What is already known about this subject The adaptive immune system has been shown to be a novel modulator of insulin resistance. Increased activation of B lymphocytes has been described in obese mice and in obese and type 2 diabetic patients. B lymphocytes promote insulin resistance by accumulating in adipose tissue and producing pathogenic antibodies. What this study adds Increased serum concentrations of IgG and IgA were found in overweight pre‐pubertal children. Increasing concentrations of IgG and IgA were in obese, but not in lean pre‐pubertal children, associated with a less favourable metabolic phenotype, consisting of increased insulin resistance and a more adverse lipid profile. Background The adaptive immune system has emerged as an unexpected modulator of insulin resistance. B lymphocytes accumulate in adipose tissue and produce pathogenic antibodies that cause insulin resistance. Objective We studied whether circulating immunoglobulins (IgG, IgA and IgM) were related to metabolic risk markers in pre‐pubertal children with and without overweight. Design and methods Subjects were 270 asymptomatic pre‐pubertal Caucasian children (145 lean, 125 overweight) recruited in a primary care setting. Assessments included serum IgG, IgA and IgM concentrations (nephelometry), insulin resistance (HOMA‐IR) and fasting lipids (triacylglycerol and high‐density lipoprotein [HDL]‐cholesterol). Results Overweight children had higher IgG and IgA serum levels than lean children (P ≤ 0.01). Increasing serum IgG and IgA, but not IgM, were associated with a less favourable metabolic phenotype, consisting of higher HOMA‐IR and triacylglycerol and lower HDL‐cholesterol, particularly in obese children, in whom serum IgG and IgA were both independently associated with HOMA‐IR (β = 0.308, P = 0.017, r2 = 9.5% and β = 0.361, P = 0.005, r2 = 13.0%, respectively) and triacylglycerol (β = 0.343, P = 0.006, r2 = 11.1% and β = 0.354, P = 0.003, r2 = 12.2%, respectively). Conclusions Increased circulating IgG and IgA in overweight children are associated with a less favourable metabolic phenotype, particularly in obese children. These results suggest a relationship between adaptive immunity and insulin resistance in childhood obesity.